SUSTAINABLE WORK-LIFE BALANCE IN IT PROFESSIONALS: A STUDY ON INNER PEACE, RESILIENCE, AND MENTAL STRESS IN INDIA’S METROPOLITAN IT HUBS - Rawat, Harish; Singh, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present research aims to analyze the correlation between Work Life Balance, Inner Peace, Resilience, and Mental Stress among IT professionals working in the metropolitan regions of India, where new advancement in technology, high performance pressure, and availability of connectivity influences the employees’ health adversely. Responding to the call for more quantitative studies to investigate WLB’s antecedents, the present study utilized a sample of 250 IT professionals to analyze the direct and indirect impact of WLB on MS through the mediating variables of IP and RES. Moderation analysis and LPA added further understanding of how such relationships change with respondent age, experience, gender and revealed that respondents can be grouped based on their levels of stress and resilience. So, the findings shown that WLB directly reduce MS and inner peace and resilience act as the mediators in between. According to the moderation analysis carried out, WLB was more useful for MS among the older and more experienced professionals. Three profiles were identified through latent profile analysis meaning recommendations could be made for specific interventions concerning each type of learner. The study emphasizes aspects such as boundary management capability, mindfulness, and general resilience trainings as mental stress reducers. This research will fill gaps within the literature about occupational health and stress resilience particularly within the Indian IT industry and informs the necessity of culturally sensitive interventions in stressful jobs. Policy and practical considerations include organizational suggestions for flexible work, mindfulness and resilience programs and work-life border policies. It is the rationale of this research for offering practical recommendations for enhancing mental health and organizational performance in stressful IT environments.